1984
DOI: 10.1210/endo-114-5-1513
|View full text |Cite
|
Sign up to set email alerts
|

Iodothyronine Deiodination Reaction Types in Several Rat Tissues: Effects of Age, Thyroid Status, and Glucocorticoid Treatment*

Abstract: Two types of iodothyronine 5'-deiodination have been characterized previously in rat tissues. They can be distinguished by inhibition of type I but not type II by 6-n-propylthiouracil, by the relative suitability of T4 and rT3 as substrates, rT3 much better than T4 for type I and T4 as good as, or better than, rT3 for type II, and by the concentration of T4 required to inhibit deiodination of rT3, 1-10 microM for type I and 1-10 nM for type II. Type I activity (6-n-propylthiouracil sensitive) is most abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 50 publications
1
25
1
1
Order By: Relevance
“…In P12 pups, however, DEX no longer affected circulating T 4 levels, whereas it significantly decreased plasma T 3 concentrations. Although previous experiments, using both adult and P7 rats, indicated that glucocorticoids reduced hepatic T 3 production (Jennings & Ferguson 1984, McCann et al 1984, our results suggested that in P12 rat pups the DEX-induced decrease in plasma T 3 levels is more likely due to the increased hepatic and possibly also renal T 3 degradation (via D3) without changes in peripheral T 3 production. A similar mechanism has been proposed to explain the glucocorticoid-induced decrease in plasma T 3 levels in man, although so far no direct experimental proof has been provided for this hypothesis (Chopra et al 1975, Westgren et al 1977, Lopresti et al 1989.…”
Section: Discussioncontrasting
confidence: 87%
“…In P12 pups, however, DEX no longer affected circulating T 4 levels, whereas it significantly decreased plasma T 3 concentrations. Although previous experiments, using both adult and P7 rats, indicated that glucocorticoids reduced hepatic T 3 production (Jennings & Ferguson 1984, McCann et al 1984, our results suggested that in P12 rat pups the DEX-induced decrease in plasma T 3 levels is more likely due to the increased hepatic and possibly also renal T 3 degradation (via D3) without changes in peripheral T 3 production. A similar mechanism has been proposed to explain the glucocorticoid-induced decrease in plasma T 3 levels in man, although so far no direct experimental proof has been provided for this hypothesis (Chopra et al 1975, Westgren et al 1977, Lopresti et al 1989.…”
Section: Discussioncontrasting
confidence: 87%
“…The finding by Osathanondh and colleagues of an increase in amniotic fluid rT3 levels in pregnant women administered DEX is consistent with this observation (35). However, McCann et al were unable to show any influence ofcorticosterone acetate on the type III 5-deiodinase system in rat liver in vitro (36). This may reflect either species variability or tissue specific regulation of type III 5-deiodinase enzyme activity.…”
Section: Resultsmentioning
confidence: 67%
“…We describe the ontogenic pattern of fetal brain 5'D-I1 activity. A previous report using rT3 as substrate (34) found very low 5'D-I1 activity in 17-day-old fetal brain, with a 3-fold increase on the day of birth. Intermediate ages were not reported.…”
Section: Discussionmentioning
confidence: 71%